2004
DOI: 10.1128/iai.72.9.4973-4984.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Response Regulator PhoP of Yersinia pseudotuberculosis Is Important for Replication in Macrophages and for Virulence

Abstract: Yersinia pestis and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
137
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(153 citation statements)
references
References 46 publications
12
137
1
Order By: Relevance
“…These data do not correlate with a report that 3 % of Y. pseudotuberculosis strain 32777 survived when challenged at pH 3.0 for 2 h (Flamez et al, 2008). It has been reported that some Y. pseudotuberculosis isolates carry non-functional alleles of phoP, which is key for survival in the acidic environment in macrophages (Grabenstein et al, 2004). Whether the difference in acid survival between strains 32777 and YpIII is due to the difference in PhoP function needs to be addressed.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…These data do not correlate with a report that 3 % of Y. pseudotuberculosis strain 32777 survived when challenged at pH 3.0 for 2 h (Flamez et al, 2008). It has been reported that some Y. pseudotuberculosis isolates carry non-functional alleles of phoP, which is key for survival in the acidic environment in macrophages (Grabenstein et al, 2004). Whether the difference in acid survival between strains 32777 and YpIII is due to the difference in PhoP function needs to be addressed.…”
Section: Discussioncontrasting
confidence: 52%
“…Although several homologues of genes such as rpoS, crp and ureABC, which are important for acid survival in other pathogenic bacteria (Castanie-Cornet et al, 1999;De KoningWard & Robins-Browne, 1995), are present in Y. pseudotuberculosis, it remains unclear which of these genes are involved in acid survival in this bacterium. PhoP (regulator of the PhoP-PhoQ system) has been shown to play a key role in survival in macrophages in Y. pseudotuberculosis (Grabenstein et al, 2004) and the two-component system regulon assay also showed that mutations of key regulator genes such as ompR (regulator of the EnvZ-OmpR system), phoP and pmrA (regulator of the PmrA-PmrB system) altered its acid survival (Flamez et al, 2008). Among these regulators, OmpR is the most important two-component regulator in the acid response since mutation of ompR decreased the acid survival of Y. pseudotuberculosis 32777 compared to other mutants, such as phoP and pmrA mutants (Flamez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously compared the substantial differences in the architecture of these systems between P. aeruginosa and Salmonella (McPhee et al, 2003), a theme that has been mirrored by studies of Yersinia Winfield et al, 2005). The Yersinia PhoP-PhoQ system is important for regulating virulence gene expression, since phoP mutants were less virulent during Y. pseudotuberculosis and Y. pestis intra-macrophage survival (Grabenstein et al, 2004). Conversely, a Salmonella strain expressing PhoP constitutively was attenuated for virulence in mice, consistent with a requirement to be able to mediate positive autoregulation (Shin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…pestis taken up by macrophages remain within a phagosomal compartment, but the bacteria inhibit the normal maturation of this phagosome to survive within the macrophage [57,59,60,62,63,83,85,86]. While the mechanisms are not well understood, Y. pestis is able to actively inhibit the acidification of this YCV [59].…”
Section: Y Pestis Interactions With Professional Phagocytesmentioning
confidence: 99%
“…However, neutrophils are better capable of killing the bacteria at this transitional stage in the bacteria's early pathogenesis [53,58,80,81]. In contrast, when a macrophage or monocyte phagocytizes Y. pestis, the bacterium prevents killing within these cells and is capable of establishing an intracellular niche [51,54,55,57,59,82,83]. In further support of this, Y. pestis infected rodents and nonhuman primates show bacteria association with macrophages, but to a lesser extent neutrophils from within the same infected host [49,53,58,84].…”
Section: Y Pestis Interactions With Professional Phagocytesmentioning
confidence: 99%